(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Subclinical thyroid dysfunction is defined as an abnormal serum thyroid-stimulating hormone level and free thyroxine and triiodothyronine levels within their reference ranges. The prevalence of subclinical hyperthyroidism is about 2 percent. Subclinical hypothyroidism is found in approximately 4 to 8.5 percent of the population. Most national organizations recommend against routine screening of asymptomatic patients, but screening is recommended for high risk populations. The management of subclinical thyroid dysfunction is controversial. There is good evidence that subclinical hypothyroidism is associated with progression to overt disease. Patients with a serum thyroid-stimulating hormone level greater than 10 mIU/L have a higher incidence of elevated serum low density lipoprotein cholesterol concentrations; however, evidence is lacking for other associations. There is insufficient evidence that treatment of subclinical hypothyroidism is beneficial. A serum thyroid stimulating hormone level of less than 0.1 mIU/L is associated with progression to overt hyperthyroidism, atrial fibrillation, reduced bone mineral density, and cardiac dysfunction. There is little evidence that early treatment alters the clinical course. DOI: 10.3329/jbcps.v26i2.4187 J Bangladesh Coll Phys Surg 2008; 26: 91-96